Analisis Skala Ekonomis Pada Produksi Kerajinan Tenun di Kabupaten Jembrana - Muliani, Ni Komang Yenigita; Saskara, Ida Ayu Nyoman (Universitas Pahlawan Tuanku Tambusai, 2024)
The craft industry is one of the industries that is being strengthened in Bali by developing weaving crafts, especially in Jembrana Regency. The aim of this research is to analyze the influence of capital, labor and raw materials simultaneously and partially on the production of the woven craft industry in Jembrana Regency as well as to analyze the economic scale and level of efficiency in the use of capital, labor and raw material inputs on the production of the woven craft industry in Jembrana Regency. This research uses an associative quantitative approach. Data collection was carried out using questionnaires and interviews. The research sample was 70 respondents, namely weaving craft entrepreneurs in Jembrana Regency. The data collected was then analyzed using multiple linear regression analysis techniques, classical assumption tests, f tests, t tests, economic scale analysis and analysis of the efficiency of using production inputs. The results of this test were processed using Eviews 12. The research results found that capital, labor and raw materials simultaneously and partially had a positive and significant effect on the production of the weaving craft industry in Jembrana Regency; The economic scale of weaving industry production in Jembrana Regency is in a state of Decreasing Return to Scale; The level of efficiency in the use of capital and raw material production factors in the production of the weaving craft industry in Jembrana Regency is not yet efficient so their use can still be increased, while the labor production factors are inefficient so their use does not need to be increased.